PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIATERHADAP KINERJA KARYAWAN AJB BUMIPUTERA 1912 - Turmono, -; Choirunisa, - (L2Dikti Wilayah III, 2020)
Human resources are the important role in the company objective achievement implementation process. This research is aimed at analyzing the influence of training and development of human resources on the performance of employees of AJB Bumiputera 1912. The population in this research is the employees of Head Office of Bumiputera 1912 totaling 229 persons and total samples determined in this research are 70 respondents, while total samples obtained and used in this research are 82 respondents using the Simple Random Sampling technique. This research uses cumulative method with parametric statistical analysis, namely multiple linier regress analysis. The obtained analysis result indicates that there is a positive and significant influence both simultaneously and partially between the training and development of HR on the performance of employees.